GROWTH AND STRUCTURE OF AG ON PD(111) STUDIED BY PHOTOELECTRON FORWARD SCATTERING USING A 2-DIMENSIONAL DISPLAY-TYPE ANALYZER - Fauster, Thomas; et al. (Physical Review B, 1993)
For an investigation of the growth and the structure of thin Ag films on Pd(111), the angular distribution of core-level photoelectrons emitted at high kinetic energy (> 500 eV) was measured with a two-dimensional display-type electron spectrometer. At room temperature, Ag grows epitaxially on Pd(111) in the layer-by-layer mode. The Ag films have fcc crystal structure and grow with a stacking fault at the interface relative to the Pd(111) substrate. Low-energy electron-diffraction-intensity measurements show that the first Ag layer is pseudomorphic with the Pd(111) substrate and the stacking fault occurs between the first and the second Ag layers.